Risk Evaluation of Ship Repair Delays with The Failure Modes and Effects Analysis (FMEA) Method - Intan Baroroh; Ndaru Gilang Ramadhan; Didik Hardianto; Tri Agung Kristiyono (International Journal of Marine Engineering Innovation and Research, 2023)
Every ship, that is still actively operating in shipping must pay attention to repair or maintenance in accordance with classification standards. This was needed by management or ship owners to carry out maintenance planning. The shipyards as repair services, there are often obstacles during the repair process that cause the repair time to be longer. This is caused by limited work equipment, delivery of materials that are not in order, and lack of technical equipment. The purpose of research is to evaluate the risk of ship repair delays so there are no failures or delays in ship repair. The method used is the FMEA method (Failure Mode and Effect Analysis) to measure each failure in each activity that affects ship repair. The results showed an assessment score in the form of a Risk Priority Number (RPN) consisting of activities: amount of cutting machines is still limited with a score of 309.83, painting and welding failures at the same time with a score of 267.08, materials that come are remachined to fit the needs with a score of 335.06 and inadequate transportation equipment with a score of 294.16. Improvements made in the form of preparing amount of work tools before the work is carried out, conditioning the order of work according to the schedule and adding backup transportation.